The establishment of exchange institutions in Uzbekistan under market reforms - Khidirov , Anvar Allayorovich (The Lingua Spectrum, 2026)
The article analyzes the establishment, formation, and development of exchange institutions in Uzbekistan under market reforms from a historical perspective. It examines the political, economic, and legal factors that influenced the emergence of exchange institutions during the transition to a market economy, the formation of the regulatory and legal framework governing their activities, and the development of exchange infrastructure. The article also analyzes the establishment and operation of commodity and stock exchanges and their role in fostering a competitive environment and developing market relations in the country. The study identifies the main stages in the establishment and institutional development of exchange institutions in Uzbekistan.